Genetic analysis of endangered hog deer (Axis porcinus) reveals two distinct lineages from the Indian subcontinent. Issue 1 (December 2018) - Gupta, Sandeep; Kumar, Ajit; Angom, Sangeeta; Singh, Bhim; Ghazi, Mirza; Tuboi, Chongpi; Hussain, Syed
Abstract The hog deer (Axis porcinus ) is threatened by habitat alteration, fragmentation, and poaching, which have led to a drastic decline of its wild population. Two subspecies ofA. porcinus have been described from its distribution range.A. p. porcinus is reported to occur from Pakistan along the Himalayan foothills through Nepal, India and Myanmar, andA. p. annamiticus is found in Thailand, Indo-China, Laos, Cambodia, and Vietnam. However, the current distribution range ofA. p. annamiticus is still unclear. We used the partial control region (CR) of mitochondrial DNA (mtDNA) and seven microsatellite loci to investigate the intra-species structure, differentiation, and demographic history of hog deer populations from three landscapes, the Terai Arc, Northeast, and Indo-Burma (Keibul Lamjao National Park (KLNP), Manipur, India) landscapes. We also carried out divergence time estimation using the complete mitogenome. The level of variation was 4%, and the time of divergence of the KLNP population and the other Indian populations was about 0.22 Mya, i.e., during the last glaciation periods of the Late Pleistocene/Early Holocene. The KLNP haplotypes of the control region were shared with the Southeast Asian subspecies, A. p. annamiticus . The results of the investigations of the microsatellite loci supported the mtDNA results unambiguously. Two genetically distinct lineages are found in India: one is found from the Terai Arc to Assam (A. p. porcinus ) and the other in Manipur (A. p. annamiticus ). The genetic diversity in KLNP was low and exhibited a higher degree of genetic differentiation compared with major Indian populations. The Bayesian skyline plots indicated that after a long phase of historic demographic stability, the populations of both the lineages of hog deer suffered pronounced declines during the period from 800 years BP to 5000 years BP. In summary, our finding provided evidence that the KLNP population is probably a prime, isolated and sustaining stock ofA. p. annamiticus and should be managed as evolutionarily significant units (ESUs).